Validating the Efficacy of an Established Micropropagation Protocol for Commercial Propagation of Neolamarckia cadamba - Wong, Sai Yan; Ho, Wei Seng; Ling, Kwong Hung (Science Alert, 2023)
Background and Objective: Micropropagation is an efficient technique for mass-producing superior clones used in establishing planted forests. However, there is a lack of comprehensive reports on the effectiveness and reliability of the established micropropagation protocol for Neolamarckia cadamba. The aim of this study was to demonstrate the effectiveness and reliability of the established micropropagation protocol for mass propagating true-to-type N. cadamba clones. Materials and Methods: Two selected candidates plus trees of N. cadamba were cultured in B5 media supplemented with 0.8 mg L–1 BAP for shoot multiplication and in ½ B5 media supplemented with 0.1 mg L–1 PBZ for root regeneration. The growth performance, the presence of phytopathogens and morphological differences were investigated. The collected data were subjected to a two-tailed t-test (p<0.05). Results: The results showed no significant variation (p<0.05) in the number of shoots regenerated from each explant compared to the reference clone N5 (B39 = 4.6, B42 = 4.3 and N5 = 4.8). Moreover, the rooting patterns of the investigated clones (B39 = 14.5 and B42 = 9.4) significantly outperformed clone N5 (6.9), with over 90% successful root regeneration. Phytopathogen analysis using ERIC-PCR assay confirmed that the in vitro regenerants were free of any phytopathogens. Additionally, histological examination revealed no significant differences between the stock plants and in vitro regenerants. Conclusion: This study successfully ascertained the effectiveness and reliability of the established micropropagation protocol for mass propagating true-to-type N. cadamba clones.